Microbe-immune interactions: new perspectives on coagulation deficiencies, purpura, and other hemorrhagic conditions under the regulation of the gut microbiota - Ren, Ruhua; Huang, Xiaohua; Wei, Diu; Guo, Qing; Wang, Chong; Li, Mengjie; Yang, Lu; Lang, Haiyan; Chen, Shana (Frontiers in Immunology, 2024)
BACKGROUND: The relationship between gut microbiota and coagulation defects, purpura, and other hemorrhagic conditions (CPH) is currently unclear, with causal links yet to be firmly established. OBJECTIVE: The causal relationships between gut microbiota and CPH, along with the potential mediating role of immune cells, were studied using Mendelian randomization analysis. METHODS: Data on 412 gut microbiota species, 731 immune cell types, and CPH were methodologically compiled from genome-wide association studies and the FinnGen database. A 2-sample Mendelian randomization approach in 2 stages was used and the causal links between gut microbiota and CPH were statistically analyzed, assessing the potential mediation by immune cells. Sensitivity and reliability were ensured through heterogeneity and pleiotropy tests. RESULTS: The abundance of Alistipes putredinis (odds ratio [OR]=0.77, 95% confidence interval [CI] 0.64–0.93, P=0.006) was negatively correlated with CPH, whereas the abundance of Bacteroides stercoris (OR=1.25, 95%CI 1.09–1.45, P=0.002) was positively correlated with the risk of CPH. There was no evidence of reverse causality or the potential mediating effects of 731 immune cell types. The abundance of Proteobacteria (OR=0.81, 95%CI 0.71–0.92, P=0.001) and Coprococcus sp. ART55/1 (OR=0.87, 95%CI 0.80–0.96, P=0.005) was negatively associated with the risk of CPH, whereas the abundance of Enterobacteriales/Enterobacteriaceae (OR=1.36, 95%CI 1.12–1.64, P=0.002) was positively correlated with the risk of CPH, with no evidence of reverse causality. Furthermore, CD38 levels on CD3-CD19 cells can serve as a mediating factor for the influence of Proteobacteria on the pathogenesis of CPH, with a mediating effect ratio of 7.26%. CONCLUSIONS: An increase in Proteobacteria abundance leads to a decrease in CD38 expression on CD3-CD19- cells, thereby reducing the risk of developing CPH. CD3 expression on naive CD4+ in mature T cells serves as a mediating factor for the influence of Enterobacteriales/Enterobacteriaceae on the pathogenesis of CPH, whereas IgD CD38br AC expression on B cells serves as a mediating factor for the influence of Coprococcus sp. ART55/1 on the pathogenesis of CPH. The mediating effect is opposite to the overall trend and has a relatively small impact. No significant heterogeneity or pleiotropy was observed.